2022
DOI: 10.3390/ijms23126463
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4 Nanozymes Improve Neuroblast Differentiation and Blood-Brain Barrier Integrity of the Hippocampal Dentate Gyrus in D-Galactose-Induced Aged Mice

Abstract: Aging is a process associated with blood–brain barrier (BBB) damage and the reduction in neurogenesis, and is the greatest known risk factor for neurodegenerative disorders. However, the effects of Fe3O4 nanozymes on neurogenesis have rarely been studied. This study examined the effects of Fe3O4 nanozymes on neuronal differentiation in the dentate gyrus (DG) and BBB integrity of D-galactose-induced aged mice. Long-term treatment with Fe3O4 nanozymes (10 μg/mL diluted in ddH2O daily) markedly increased the doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…A study by Yan et al showed that the addition of the PEG-modified Fe 3 O 4 nanozyme to mouse chow, reduced neuronal damage due to ischemic stroke and maintained the integrity of the BBB. A study by Xia et al showed the same conclusion that long-term use of the PEG-modified Fe 3 O 4 nanozyme (10 μg/mL per day, ddH 2 O dilution) significantly improved the immunoreactivity of double corticosteroid (DCX) and reduced d-galactose-induced BBB damage.…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 77%
“…A study by Yan et al showed that the addition of the PEG-modified Fe 3 O 4 nanozyme to mouse chow, reduced neuronal damage due to ischemic stroke and maintained the integrity of the BBB. A study by Xia et al showed the same conclusion that long-term use of the PEG-modified Fe 3 O 4 nanozyme (10 μg/mL per day, ddH 2 O dilution) significantly improved the immunoreactivity of double corticosteroid (DCX) and reduced d-galactose-induced BBB damage.…”
Section: Therapeutic Application Of Disease Microenvironment Remodeli...mentioning
confidence: 77%
“…The strong antioxidant qualities of IONPs in postponing animal aging and reducing ROS-induced neurotoxicity were further confirmed by the Drosophila AD model [301]. Fe 3 O 4 nanozymes showed a potent mitigative effect against d-galactose-induced oxidative damage of the neuroblast as well as apoptosis and autophagy in the hippocampal dentate gyrus [303]. IONPs showed potential application in the diagnosis and treatment of different neurodegenerative diseases, such as AD, PD, and ALS [304].…”
Section: Iron-based Nps (Ionps) and Their Antioxidant Conjugates To A...mentioning
confidence: 82%
“…An imbalance leading to excessive ROS levels can result in increased oxidative stress, which is implicated in various diseases and aging-related processes. Conditions commonly associated with oxidative stress include neurodegenerative diseases, , cardiovascular diseases, , and inflammatory disorders (Figure ). Most notably, SAzymes, mimicking peroxidase (POD), oxidase (OXD), catalase (CAT), and superoxide dismutase (SOD), hold the potential for modulating ROS levels in regeneration medicine (Figure ).…”
Section: Mechanism Of Sazymesmentioning
confidence: 99%